Are Mindfulness‐Based Interventions as Effective as Cognitive Behavioral Therapy in Reducing Symptoms of Complicated Perinatal Grief? A Systematic Review - Dolan, Niamh; Grealish, Annmarie; Tuohy, Teresa; Bright, Ann‐Marie (Journal of midwifery & women's health, 2022)
Introduction Perinatal loss can be a devastating experience for parents that can result in complicated grief symptoms that include depression, anxiety, and posttraumatic stress. Perinatal bereavement care pathways have been developed internationally within health care services; however, there is an apparent lack of recommendations and guidance on grief‐focused interventions specifically for complicated perinatal grief. Studies have analyzed the effectiveness of cognitive behavioral therapy (CBT) for perinatal grief, and more recent research has emerged on the use of mindfulness‐based interventions (MBIs) for perinatal grief symptoms. The purpose of this study was to conduct a systematic review and present the effectiveness of CBT and MBIs for perinatal grief, to report patient experiences of the interventions, and to determine which intervention can be more effective in managing symptoms of complicated perinatal grief. Methods A systematic search was conducted of 5 academic databases: PsycINFO, CINAHL, MEDLINE, Social Science, and ASSIA. No limits on publication date, language, or geographic location were set because of the paucity of research published on this subject. Quality appraisal was conducted for each included study. Findings are reported in accordance with the PRISMA statement. Results This systematic review identified 8 eligible studies with a total of 681 bereaved participants. The results were examined for effectiveness of CBT and MBIs for grief; effectiveness of CBT and MBIs for depression, anxiety, and posttraumatic stress; and participant experiences. Both interventions produced favorable reductions of perinatal grief symptoms, depression, and posttraumatic stress. However, a true comparison between the 2 interventions’ effect on complicated perinatal grief symptoms could not be made because of the limited studies in this area and the heterogeneity of the included studies’ methods and outcomes. Discussion Both MBIs and CBT interventions can be effective in reducing symptoms of complicated perinatal grief. The findings of this review are heavily weighted in quantitative outcome measurements. More qualitative research and randomized controlled trials with larger sample sizes are needed in this area of perinatal bereavement care.